Fachlichkeit in Lernwerkstätten Kind und Sache in Lernwerkstätten - Peschel, Markus; Kelkel, Mareike (Lernen und Studieren in Lernwerkstätten, 2018)
The volume asks about the specific subject matter in different workshops: What is "the thing" that is dealt with in workshops? What is the importance of "the thing" in the context of pedagogical support? How is "the matter" approached from a pedagogical point of view? How does a subject matter influence the pedagogical approach in learning workshops? Learning workshop work must meet these dual demands in order to enable children to encounter things in an educationally effective way. In the articles in this volume, the authors describe their focus on "the thing" in their learning workshops from different professional, didactic and pedagogical perspectives.